Perencanaan Partisipatif Tanggap Darurat Bencana Tsunami Di Pesisir Selatan Watulimo, Trenggalek - Fadly Usman; Septiana Hariyani; Fadhilatus Shoimah (TATALOKA, 2021)
The research aims to mapping the tsunami-prone areas in Watulimo District using numerical simulation methods and spatial analysis as well as compiling tsunami response planning by determining shelters and evacuation routes in a participatory manner according to the characteristics of residents local wisdom of Watulimo District using weighting analysis and network analysis with ArcGIS. The most prone area to tsunami is Prigi Village because it has the lowest topography compared to the other two villages. Determination of shelter is carried out by considering the building function, number of floors, building area, building capacity, distance from the coastline, location from the road, and building construction. Public facilities with the number of floors >1 such as flat, trade facilities; religious facilities; educational facilities; government facilities; as well as health facilities in Watulimo District can be used as shelters during tsunami. Based on the analysis, the shelters obtained can accommodate the population in tsunami-prone areas. The evacuation route can be determined by considering the distance, road width, road conditions, road class, and travel time to obtain the fastest route from settlement to the nearest shelter. The evacuation routes that can be used in Watulimo District are the existing roads. However, there is a need for road repairs in damaged/ potholed road conditions, road widening, adding new roads to facilitate the evacuation process of disaster victims to the shelter, and carrying out routine road maintenance on roads that will be used as evacuation routes, so that these roads are always in good condition.